Chiral Arene Ruthenium Complexes. 6. Diastereoselective Formation of Chiral-At-Metal P-Tethered Arene Ruthenium(II) Complexes - Zenneck, Ulrich; et al. (Organometallics, 2004)
The easily accessible (R)-3-phenylbutanol (1) can be transformed into the novel enantiopure ligand diphenyl((R)-3-phenylbutyl)phosphane (3). 3 splits the complex dimer [RuCl2(η6-C6H5CO2 Me)2] (6) by adding as a σ-ligand to form mononuclear [RuCl2(η6-C6H5COOMe)-((R)- η1-PPh2(CH2)2 CH(CH3)Ph)] (7). An intramolecular arene ligand displacement reaction leads to [RuCl2((R)-η1-PPh2 (CH2)2CH(CH3)-η6-C6 H5)] (8) with a tethered side chain of the arene ligand. Nucleophilic substitution of a chloride ligand by primary or secondary amines with the assistance of NaBF4 gives access to the diastereomeric complex salts [RuCl(amine)-((R)-η1-PPh2(CH2)2C H(CH3)-η6-C6H5)] BF4. Good diastereoselectivities were obtained for aniline, piperidine, benzylamine, and butylamine complex salts 9-12 (de = 82-90%). The absolute structures of 8-10 have been determined by X-ray structure analysis. SRu,RC configurations were found for the major diastereomers of aniline and piperidine complex salts 9 and 10. Not only the side chain stereogenic center but also the metal configuration of the cation of salt 9 is stable for longer periods at low and at elevated temperatures in different solutions.
UnivIS-Import:2017-11-07:Pub.2004.forsch.sonder.sfb583.chiral